Simulasi Virtual Private Network Dengan Topologi Star - Anggie Maulia; Aldi Fadilla Ramadhan; Andi Purwanto; Apipah Apipah; Didik Aribowo (Jurnal Penelitian Teknologi Informasi dan Sains, 2024)
Virtual Private Network (VPN) is a form of private network through a public network by focusing on the security of the encrypted data in it. This research uses Cisco Packet Tracere software as a computer network technology simulation tool. Cisco Packet Tracker is a device in network technology simulation that functions for creation and development in networks. The purpose of this research is to create a VPN simulation using a star topology with Cisco Packet Tracer software. Star topology is a star-shaped topology, where each node is to the centre. The method used is a qualitative method with data collection techniques or Literature Study, namely looking for references from the internet in the form of journals. In creating a VPN simulation using Cisco Packet Tracer requires hardware in the form of a server, router, switch, and PC or computer.